Perbedaan Pengaruh Model Latihan Konsentrasi Dan Tanpa Model Latihan Konsentrasi Terhadap Peningkatan Kemampuan Shooting Game Atlet Petanque Undikma - Lubis, Muhammad Ridwan; Permadi, Andi Gilang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This research is motivated by the inconsistency in the shooting ability of athletes in shooting games in Petanque sports, both at the regional and national levels. This study aims to determine the effect of the concentration training model on the improvement of the shooting game ability of Undikma Petanque athletes. This study used an experimental method with the design of "two group pretest posttest design". The instruments used for the shooting ability test were the shooting station numbers 1, 2, 3, 4, and 5 with a distance of 6 meters, 7 meters, 8 meters, and 9 meters. The subjects in this study were 14 Undikma Petanque athletes. Samples were taken from the purposive sampling. Based on the results of the t-test analysis showed the same significant results between the concentration training model and without concentration training. However, the concentration training model results are better than without the concentration training model seen with the average value of shooting using the pretest concentration training model results of 4.71 increased by 13.00. The amount of increase was 8.28. Without the concentration training model, the initial pretest average result was 3.42 and increased to 10.00. The amount of increase was 6.57. The difference in the average shooting game result increment with the concentration training model, and without the concentration training model is 1.71.